Well-Structured Agribusiness Linkages Projects Lead to Happy Clients and a Developed Sector - Menkova, Viktoryia; Sethi, Sanwaree (World Bank, Washington, DC, 2012)
Despite the large potential of the agricultural sector in Eastern Europe and Central Asia, production is still limited by a lack of technical knowledge and, in many cases, an unwillingness to change agricultural practices inherited from Soviet times. The problem has more than one cause: poor technology, management skills, and quality of produce prevent farms from joining agribusiness supply chains. Limited access to financing further prevents farmers who want to improve practices from making the investments needed to achieve better productivity and efficiency. This situation is further complicated by an unfriendly regulatory environment, specifically, land ownership issues and corrupt state subsidies systems, which distort the market. International Financial Corporation (IFC) Private Enterprise Partnership in Eastern Europe and Central Asia (IFC PEP-ECA) has developed a comprehensive approach to tackling each of these issues in its agribusiness projects; this approach has also been affirmed by the independent evaluation group.